Assessing the Health Impact of Trade: A Call for an Expanded Research Agenda; Comment on "The Trans-Pacific Partnership: Is It Everything We Feared for Health?" - Courtney McNamara (Kerman University of Medical Sciences, 2017)
Labonté et al provide an insightful analysis of the Trans-Pacific Partnership (TPP) and its impact on a selection of important health determinants. Their work confirms concerns raised by previous analyses of leaked drafts and offers governments serious and timely reasons to carefully consider provisions of the agreement prior to moving forward with ratification. It also contributes more generally to a growing literature focused on identifying the health impacts of trade. This commentary uses the authors' analysis as a starting point to reflect on two interrelated issues relevant both for taking seriously one of the article's main recommendations and future work in the area of trade and health.